Mathematical Representations of Students with Dyscalculia in Differentiated Learning Environments: A Conceptual Review - Fatqurhohman, Fatqurhohman; Malini, Adnan Noor; Mendyas, Ferdiano (SMARTH: Journal of Mathematics Education and Learning, 2025)
Students with dyscalculia experience persistent difficulties in numerical processing, number sense, relational understanding, and arithmetic procedures, which negatively affect their cognitive, affective, social, and functional development. Conventional mathematics instruction often fails to accommodate these diverse needs, resulting in low engagement, heightened mathematics anxiety, and weak conceptual understanding. This conceptual review synthesizes research on mathematical representation strategies for students with dyscalculia within differentiated learning contexts, with an emphasis on evidence-based approaches that support conceptual understanding and flexible problem solving. A comprehensive review of relevant scholarly literature was conducted, focusing on multimodal representations (concrete, pictorial, and symbolic) integrated within differentiated instruction and Universal Design for Learning (UDL) frameworks. The analysis highlights studies examining cognitive, affective, and functional outcomes in mathematics learning for students with dyscalculia. The findings indicate that the use of multimodal representations combined with differentiated learning reduces cognitive load, supports the progression from concrete to abstract thinking, and enhances problem-solving flexibility. In addition, these approaches help reduce mathematics anxiety, increase student engagement, strengthen self-confidence, and foster a more positive mathematical identity. This review proposes a conceptual framework to guide educators, parents, and practitioners in designing adaptive, inclusive, and evidence-based interventions, contributing to more equitable and sustainable mathematics instruction for students with dyscalculia.